Training on Making "Anchovy Potato Chips" to Encourage Entrepreneurship Mindset of Local Housewife in Silalas Village Medan - Edison Parulian; Lenny Menara Sari Saragih; Lusiah Lusiah; Tarwiyah Tarwiyah; Corinna Wongsosudono (International Journal Of Community Service, 2023)
The training activity of making chips for housewives of Silalas village in West Medan conducted at IBBI University is one of the activities of the partnership-based UMKM development program. This training activity was carried out from the presentation and strengthening of material on entrepreneurship and also finance and sanitation for housewives. Activities other than transferring entrepreneurial knowledge and also direct practice of making chips are also a place for friendship and have a positive impact on broadening the horizons of academics. The results of the training activities carried out are expected to increase entrepreneurial interest among housewives and also improve skills to create small businesses and increase family income.